2020
DOI: 10.21203/rs.3.rs-70179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosomes from Adipose Tissue-Derived Mesenchymal Stem Cells Ameliorate Histone-Induced Acute Lung Injury by Activating the PI3K/Akt Pathway in Endothelial Cells.

Abstract: BackgroundMesenchymal stem cells (MSCs), including adipose-derived mesenchymal stem cells (ADSCs), have been shown to attenuate organ damage in acute respiratory distress syndrome (ARDS) and sepsis; however, the underlying mechanisms have not been fully understood. In this study, we aimed to explore the potential roles and molecular mechanisms of action of ADSCs in histone-induced endothelial damage. MethodsMale C57BL/6N mice were intravenously injected with ADSCs, followed by histones or a vehicle. The mice i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In this study, as a significantly downregulated gene, THBS1 might play an important part in the prognosis of septic shock through the PI3K-Akt signaling pathway. Mizuta et al [31] suggested that activating the PI3K/Akt signaling pathway contributes to suppressing endothelial apoptosis, inhibits lung hemorrhage and edema, and improves murine survival. The morbidity and mortality caused by myocardial infarction might be decreased via the stimulation of the PI3K/Akt-dependent cascade [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as a significantly downregulated gene, THBS1 might play an important part in the prognosis of septic shock through the PI3K-Akt signaling pathway. Mizuta et al [31] suggested that activating the PI3K/Akt signaling pathway contributes to suppressing endothelial apoptosis, inhibits lung hemorrhage and edema, and improves murine survival. The morbidity and mortality caused by myocardial infarction might be decreased via the stimulation of the PI3K/Akt-dependent cascade [32].…”
Section: Discussionmentioning
confidence: 99%
“…The various components of MSC-derived exosomes can exert anti-inflammatory effects and antiapoptotic effects and promote cell regeneration [47][48][49][50]. For example, such exosomes may exert protective effects against sepsisinduced ALI or ARDS by transferring nucleic acids including mRNAs, long noncoding RNAs, and microRNAs [21] that modulate the MAPK signaling pathway to affect the levels of proinflammatory cytokines in the lung tissue [23] and by transferring other biological components such as mitochondrial or intracellular proteins [51]. Our study suggests that hMSCs from the three tissue sources, in particular those derived from the adipose tissue, and their secreted exosomes can exert pulmonary protective effects by inhibiting glycolysis of alveolar macrophages, thereby promoting macrophage M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-derived exosomes show organ-protective functions that depend on their cellular origin and MSC culture conditions (e.g., seeding density), as well as the method and timing of collection [20]. Although previous work investigated the use of various MSC-derived exosomes in the treatment of sepsis-induced ALI [21][22][23], cross-sectional comparative studies of the lung-protective capacity of exosomes derived from different human MSCs (hMSCs) in sepsis-induced ALI are lacking. Therefore, the present study is aimed at comparing hMSCs from adipose tissue, bone marrow, or umbilical cord as well as their secreted exosomes for their ability to protect against sepsis-induced ALI in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from ASCs transport an abundance of proteins, lipids, ribonucleic acids, and genomic and mitochondrial DNA and play a crucial role in intercellular communication [38]. Numerous studies have demonstrated that exosomes derived from ASCs can promote the proliferation and migration of ECs, induce the formation of vascular-like structures in vitro, and promote angiogenesis in animals [39][40][41]. In addition, they have exhibited good efficacy in flap repairment [40] and the treatment of kidney ischemiareperfusion injury [42], myocardial infarction [43], cerebral ischemia [44], lung injury [41,45], and diabetic limb ischemia [39].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that exosomes derived from ASCs can promote the proliferation and migration of ECs, induce the formation of vascular-like structures in vitro, and promote angiogenesis in animals [39][40][41]. In addition, they have exhibited good efficacy in flap repairment [40] and the treatment of kidney ischemiareperfusion injury [42], myocardial infarction [43], cerebral ischemia [44], lung injury [41,45], and diabetic limb ischemia [39]. However, reports showed that different cell sources [40] and treatment conditions [46][47][48] could affect the quantity and composition of exosomes.…”
Section: Discussionmentioning
confidence: 99%